ENHANCEMENT OF PHOTON AND NEUTRON IMAGES BY DENOISING USING STATIONARY WAVELET TRANSFORM - A. M. Osman
The noises introduced during the experimental procedure greatly affect the detection capability of measuring system. In this paper, a new approach to deal with the noise inherent with neutron back scattering, NBS, and transmission imaging process is presented. The image noises are eliminated using the Stationary Wavelet Transform, SWT, with time invariant characteristic which is particularly useful in image denoising. The test results of SWT on images obtained by NBS and transmission techniques have shown an enhanced images quality. The results also show that SWT has a superior performance than the widely used adaptive Matched Filter Method, MFT.
Keywords: Physics; Optics